Relationship between neutrophils to HDL-C ratio and severity of coronary stenosis - Tuli Kou; Haorou Luo; Lixue Yin (BMC Cardiovascular Disorders, 2021)
Abstract Background Lipid and inflammatory molecules play a key role in the development of inflammation. Neutrophil counts are used as markers of inflammation duration, and HDL-C is used as an anti-atherosclerosis component. However, few studies have been found to integrate these two indicators to explore coronary stenosis. We suggested that neutrophil count as a marker of inflammation persistence and HDL-C as an anti-atherosclerotic component should be integrated into a single biomarker NHR to explore its correlation with CAD degree and predict the severity of coronary stenosis among CAD patients. Methods We examined 404 eligible patients who underwent coronary angiography. Based on the results of coronary angiography, patients in CAD+ group (n = 155) were defined as those having angiographic coronary stenosis of at least 50% lumen reduction in at least one major coronary artery (including left anterior descending artery, left circumflex artery, left main coronary artery, right coronary artery). Patients with luminal stenosis but no more than 50% were defined as CAD− group (n = 49), and patients without luminal stenosis (n = 200) were regarded as control group. The relationship between various serum markers and the severity of coronary stenosis was examined by Spearman correlation analysis. Logistic regression analysis was performed to identify the influencing factors of the severity of coronary artery disease. Results The modified Gensini score was positively correlated with neutrophil HDL-C ratio and negatively correlated with albumin and HDL-C. Multiple regression analysis showed that neutrophil HDL-C ratio were significantly associated with CAD. Neutrophil HDL-C ratio is an independent predictor of CAD. The ROC analysis provided a cut-off value of 1.51 for neutrophil HDL-C ratio to predict CAD with 94.8% sensitivity and 0.024 Yoden index, and area under the ROC curve of 0.617 (95% CI 0.560–0.675, P < 0.001). Conclusion Neutrophil HDL-C ratio is not only closely related to coronary artery stenosis, but also an independent predictor of severe coronary stenosis.